The Evolution of Literary Canons: Coetzee's 'What is a Classic?' in the Contemporary Context (Literary Voice, 2024)
J. M. Coetzee, a South African-born writer, is renowned for his sparse yet potent prose. His writing often delves into complex themes such as apartheid, colonialism, and the human condition with a stark, introspective style. Through his precise and evocative prose, he explores the depths of human experience, inviting readers to confront uncomfortable truths about society and the self, and he even writes about the fundamental themes of literature. He examines the development of Johann Sebastian Bach's reputation as a classic from a critical standpoint in his famous essay "What is a Classic," drawing parallels with contemporary writing. Coetzee's research provokes reflection on the procedures and complexities of declaring a piece of writing a classic. Discussions about the creation of canons, cultural identity, and historical conditioning continue to influence opinions on classic literature in the contemporary literary landscape. Coetzee's admittance that our historical background influences how we play and interpret Bach's music provides a critical perspective on the subjectivity that permeates classical composition interpretation. Coetzee's research provokes reflection on the procedures and complexities of declaring a piece of writing a classic. Discussions about the creation of canons, cultural identity, and historical conditioning continue to influence opinions on classic literature in the contemporary literary landscape. Through a close reading of the selected essay from the book, the paper will analyse Coetzee's reflections on the nature of the classic, his critique of canonical thinking, and his exploration of the tensions between tradition and innovation in literary discourse.
Keywords: Literary Canons, J.M. Coetzee, Johann Sebastian Bach, historical context, Horatian.